2024
DOI: 10.1001/jamasurg.2023.5951
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Mortality Following Surgery in Patients With a Previous Cardiovascular Event

Christos V. Chalitsios,
Matthew S. Luney,
William A. Lindsay
et al.

Abstract: ImportanceThere is a lack of consensus regarding the interval of time-dependent postoperative mortality risk following acute coronary syndrome or stroke.ObjectiveTo determine the magnitude and duration of risk associated with the time interval between a preoperative cardiovascular event and 30-day postoperative mortality.Design, Setting, and ParticipantsThis is a longitudinal retrospective population-based cohort study. This study linked data from the Hospital Episode Statistics for National Health Service Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Leveraging an administrative data source of 21 million procedures, Chalitsios et al found an increased risk of mortality after surgery that persisted for up to 14 months after an event with elective surgery (odds ratio = 1.22 [95% CI, 1.06-1.39] for procedures within 6-12 months) and 7 months with emergent surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leveraging an administrative data source of 21 million procedures, Chalitsios et al found an increased risk of mortality after surgery that persisted for up to 14 months after an event with elective surgery (odds ratio = 1.22 [95% CI, 1.06-1.39] for procedures within 6-12 months) and 7 months with emergent surgery.…”
mentioning
confidence: 99%
“…As demonstrated in Table 1 in the Chalitsios et al article, surgical procedures among patients with a prior cardiovascular event are markedly different from the typical surgical procedure. Patients with a prior cardio- or cerebrovascular event are already at an increased risk of mortality, regardless of whether they have surgery or not .…”
mentioning
confidence: 99%